Upaya Meminimalisir Kecelakaan Kerja Di Area Penambangan PT. Prima Sarana Gemilang Jobsite Muara Alam Sejahtera, Kabupaten Lahat, Provinsi Sumatera Selatan - Tomy Efraim Situmorang; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Unsafe conditions and unsafe actions at PT. Prima Sarana Gemilang are the main causes of accidents that cause loss and loss to humans and companies, damage to equipment, disrupt production and others. Based on the results of the study, it is known that work locations with high potential hazard at PT. Prima Sarana Gemilang Jobsite Muara Alam Sejahtera is a Loading Point with 4 accidents in that area, based on the results of the study, it was found that 54 respondents answered that physical hazards, ergonomic hazards and psychological hazards (100%) were found in the mining area, based on the research conducted, it is known that, of the 54 respondents who explained bad knowledge, 33 respondents (61.1%), based on the results of the study it was found that 54 respondents answered the control hierarchy with PPE was the most done, based on the results of a study of 54 respondents who answered the effort to minimize workplace accidents by management, the most widely done was that workers were given directions on how to properly use PPE and maintain PPE so that it was always in good condition. Keywords: Hazard Potential, Hazard Control Hierarchy, Work Accident Management, Safety, JSA and JHA.